2018
DOI: 10.3389/fimmu.2018.00082
|View full text |Cite
|
Sign up to set email alerts
|

Negative Effect of Age, but Not of Latent Cytomegalovirus Infection on the Antibody Response to a Novel Influenza Vaccine Strain in Healthy Adults

Abstract: Older adults are more vulnerable to influenza virus infection and at higher risk for severe complications and influenza-related death compared to younger adults. Unfortunately, influenza vaccine responses tend to be impaired in older adults due to aging of the immune system (immunosenescence). Latent infection with cytomegalovirus (CMV) is assumed to enhance age-associated deleterious changes of the immune system. Although lower responses to influenza vaccination were reported in CMV-seropositive compared to C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 54 publications
(77 reference statements)
2
24
0
Order By: Relevance
“…CMV-specific CD4 + T cells are thought to play an important role in containing CMV infection, and in mouse models, CD4 + T cells were abundant in infected peripheral tissues (Reuter et al, 2005;Verma et al, 2015). A reduction in the CD4:CD8 ratio in healthy young CMV + adults, which has also been reported in other studies (Turner et al, 2014), could be caused by a reduction in circulating CD4 + T cells as they are recruited to peripheral sites of infection. As infected individuals age, multiple reactivation events over many decades cause a gradual expansion of CMV-specific CD8 + T cells, which then become the prominent factor driving the CD4:CD8 ratio down (Hadrup et al, 2006).…”
Section: Resultssupporting
confidence: 59%
See 1 more Smart Citation
“…CMV-specific CD4 + T cells are thought to play an important role in containing CMV infection, and in mouse models, CD4 + T cells were abundant in infected peripheral tissues (Reuter et al, 2005;Verma et al, 2015). A reduction in the CD4:CD8 ratio in healthy young CMV + adults, which has also been reported in other studies (Turner et al, 2014), could be caused by a reduction in circulating CD4 + T cells as they are recruited to peripheral sites of infection. As infected individuals age, multiple reactivation events over many decades cause a gradual expansion of CMV-specific CD8 + T cells, which then become the prominent factor driving the CD4:CD8 ratio down (Hadrup et al, 2006).…”
Section: Resultssupporting
confidence: 59%
“…Although a range of studies have shown contradictory findings on the impact of CMV on immune responses, with some demonstrating a negative effect (Trzonkowski et al, 2003;Derhovanessian et al, 2013;Turner et al, 2014;Frasca et al, 2015;Wagner et al, 2018), some a positive effect (Miles et al, 2008;Holder et al, 2010;Wald et al, 2013;Furman et al, 2015), and others no effect (den Elzen et al, 2011;O'Connor et al, 2014), it is likely that a combination of factors contributes to these differing results. First, the impact of CMV on heterologous immune responses may differ between primary and memory responses.…”
Section: Resultsmentioning
confidence: 99%
“…The efficacy of response to vaccine challenge has been used as a surrogate of immune competence in many studies and an impairment of influenza-specific antibody titre has been reported (62)(63)(64). However, other studies have failed to show any association between CMV carriage and either the breadth or titre of neutralising antibodies (65)(66)(67). As such, the importance of CMV infection as a determinant of immune competence remains uncertain.…”
Section: Infection In Older People Is Associated With An Excess Omentioning
confidence: 99%
“…Whether progressive EM T-cell differentiation is a non-functional response against the persistent presence of CMV antigens or a functional adaptation of the CMV-reactive T cells to keep control over CMV infection is unknown, but it may affect cellular function and senescence. In humans, latent CMV infection in older individuals resulted in lower protection rates after vaccination with an influenza vaccine 30 32 ; however, neutral effects of CMV infection were also observed 33 36 . Possibly related to some of these studies is the finding that high-dose but not low-dose CMV infection impairs the development of a heterologous anti-viral T-cell response 24 , 37 , 38 .…”
Section: Progressive Differentiation Of Cytomegalovirus-specific Effementioning
confidence: 99%